2019
DOI: 10.1007/s13753-019-00230-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Livelihood Vulnerability to Drought: A Case Study in Dak Nong Province, Vietnam

Abstract: In recent years, droughts have strongly affected the Central Highlands of Vietnam and have resulted in crop damage, yield decline, and serious water shortage. This study investigated the livelihood vulnerability of five communities of farmers who are exposed to droughts in one of the more vulnerable regions of Vietnam-Dak Nong Province. A survey of 250 households was conducted in the five communities to collect data on the region's sociodemographic profile, livelihood systems, social networks, health status, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Moreover, many women are vulnerable to climate variability as they are on the frontline of rural development, which is normally agro-based (Nellemann et al, 2011;Sharma, 2016). Thao et al (2019) found that people who relied on unreliable water sources and poor livelihood strategies in Vietnam rural areas were highly vulnerable to the impacts of droughts, which is similar to the findings of Chigavazira (2019) in her study in Zimbabwe. Rao et al (2019) cautioned though that women should not be seen universally as victims to climate variability rather there is need to unpack power relations issues, inclusion and exclusion in decision-making processes and challenge cultural beliefs that have perpetuated inequalities.…”
Section: The Problemsupporting
confidence: 80%
“…Moreover, many women are vulnerable to climate variability as they are on the frontline of rural development, which is normally agro-based (Nellemann et al, 2011;Sharma, 2016). Thao et al (2019) found that people who relied on unreliable water sources and poor livelihood strategies in Vietnam rural areas were highly vulnerable to the impacts of droughts, which is similar to the findings of Chigavazira (2019) in her study in Zimbabwe. Rao et al (2019) cautioned though that women should not be seen universally as victims to climate variability rather there is need to unpack power relations issues, inclusion and exclusion in decision-making processes and challenge cultural beliefs that have perpetuated inequalities.…”
Section: The Problemsupporting
confidence: 80%
“…Through this study, two main contributions are made to the literature. First, the previous vulnerability studies mainly focused on other natural disasters, including flooding and droughts [52][53][54][55][56], rather than NFLD. However, as a prominent environmental issue, NFLD is of significance as a research subject.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…K-Means Clustering shows six groups, each of which has similar zone's characteristics (Figure 11). The largest, cluster 2, has six zones (1,6,7,21,22,24), and the smallest, cluster 4, has three zones (2,3,4). Most of the zones are located in the middle area of the MKB.…”
Section: Clustering Time Seriesmentioning
confidence: 99%
“…Drought is among those natural disasters that have caused severe damage to humanity, society, economy, and environment [1][2][3][4][5][6]. In the three recent decades, droughts have occurred in many countries across the world, such as the United States [7], Brazil [8], China [9], and Vietnam [10].…”
Section: Introductionmentioning
confidence: 99%